Implementing VersaStack with Cisco ACI Multi-Pod and IBM HyperSwap for high availability - Saini, Jaswinder Singh (IBM Corporation, International Technical Support Organization, 2018)
The IBM HyperSwap® high availability (HA) function allows business continuity in a hardware failure, power failure, connectivity failure, or disasters, such as fire or flooding. It is available on the IBM SAN Volume Controller and IBM FlashSystem products. This IBM Redbooks publication covers the preferred practices for implementing Cisco VersaStack with IBM HyperSwap. The following are some of the topics covered in this book: Cisco Application Centric Infrastructure to showcase Cisco's ACI with Nexus 9Ks Cisco Fabric Interconnects and Unified Computing System (UCS) management capabilities Cisco Multilayer Director Switch (MDS) to showcase fabric channel connectivity Overall IBM HyperSwap solution architecture Differences between HyperSwap and Metro Mirroring, Volume Mirroring, and Stretch Cluster Multisite IBM SAN Volume Controller (SVC) deployment to showcase HyperSwap configuration and capabilities This book is intended for pre-sales and post-sales technical support professionals and storage administrators who are tasked with deploying a VersaStack solution with IBM HyperSwap.
"Storage.". - Number on back cover: SG24-8423-00. - Includes bibliographical references. - Online resource; title from cover (Safari, viewed October 9, 2019)
Keywords: Storage area networks (Computer networks); Information technology -- Management; Database management -- Software; Information retrieval; Information Storage and Retrieval; Database Management Systems; Réseaux de stockage (Informatique); Technologie de l'information; Gestion; Bases de données; Gestion; Logiciels; Recherche de l'information; information retrieval; Database management; Information technology; Management; Software